Longitudinal changes of thoracic aortic diameters in the general population aged 55 years or older. Issue 22 (28th April 2022) - Thijssen, Carlijn G E; Mutluer, Ferit O; van der Toorn, Janine E; Bons, Lidia R; Gökalp, Arjen L; Takkenberg, Johanna JM; Mokhles, Mostafa M; van Kimmenade, Roland R J; Vernooij, Meike W; van der Lugt, Aad; Budde, Ricardo P J; Roos-Hesselink, Jolien W; et al.
Abstract : Objective: Longitudinal data on age-related changes in the diameters of the thoracic aorta are scarce. To better understand normal variation and to identify factors influencing this process, we aimed to report male-female-specific and age-specific aortic growth rate in the ageing general population and identify factors associated with growth rate. Methods: From the prospective population-based Rotterdam Study, 943 participants (52.0% females, median age at baseline 65 years (62–68)) underwent serial non-enhanced cardiac CT. We measured the diameters of the ascending (AA) and descending aorta (DA) at two time points and expressed absolute and relative differences. Linear mixed effects analysis was performed to identify determinants associated with change in aortic diameters. Results: Mean AA diameter at baseline was 37.3±3.6 mm in male population and 34.7±3.2 mm in female population, mean DA diameter was 29.6±2.3 in male population and 26.9±2.2 mm in female population. The median absolute change in diameters during follow-up (mean scan interval 14.1±0.3 years) was 1 mm (0–2) for both the AA and DA. Absolute change per decade in AA diameter was significantly larger in males than in females (0.72 mm/decade (0.00–1.43) vs 0.70 mm/decade (0.00–1.41), p=0.006), as well as absolute change in AD diameter (0.71 mm/decade (0.00–1.42) vs 0.69 mm/decade (0.00–1.36), p=0.008). There was no significant difference between male and female population in relative change of their aortic diameters during follow-up. Age, male sex, higher body mass index (BMI) and higher diastolic blood pressure (DBP) showed a statistically significant independent association with increase in AA and DA diameters over time. Conclusions: Some degree of increase in thoracic aortic diameters is typical in both men and women of an aging population. Factors associated with this change in thoracic aortic diameters were sex, age, BMI and DBP.